Penguatan Literasi Keuangan dan Pasar Modal Bagi Generasi Z di SMAM 8 Gresik: Strengthening Financial Literacy and Capital Markets For Generation Z at SMAM 8 Gresik - Alriansyah Manurung, Muhammad Rizqi (JURNAL PENGABDIAN MANAJEMEN, 2026)
This community service program aims to enhance financial literacy and capital market awareness among Generation Z students through an educational initiative conducted at SMA Muhammadiyah 8 Gresik. The low level of financial literacy among adolescents, combined with increasing access to digital financial platforms, highlights the urgent need for structured and comprehensive financial education. The program was carried out in a full-day session through a seminar, material presentation, and interactive discussions that encouraged active participation from students. The activity began with a pre-test to measure students’ initial understanding, followed by sessions covering fundamental concepts of financial literacy, financial planning, capital market instruments, and investment risk management. Students demonstrated a high level of enthusiasm, particularly during the question-and-answer session, where many expressed interest in learning practical and safe investment strategies suitable for beginners. Post-test results indicated a significant improvement in students’ comprehension, especially regarding the differences among investment instruments, the mechanisms of the capital market, and the importance of making informed and responsible investment decisions. This program successfully increased students’ awareness of the importance of financial management from an early age and fostered their interest in exploring investment opportunities more thoughtfully. Overall, the initiative contributed positively to strengthening financial literacy within the school environment and may serve as a model for similar educational programs in other institutions.